A Study on Online Discount Couponing Industry in India - Shome, Samik; Roy, Aindrila (Indian Journal of Marketing, 2012)
There has been a lot of buzz and activity in and around the discount couponing industry in India for the last couple of years. Though couponing has already taken the form of a revolution in the developed world, the developing nations in the likes of India are yet to catch up with the development. In this connection, the paper is an attempt to study the Indian discount couponing industry in terms of its modus operandi, competitive structure as per Porter’s framework, business potential and growth. The results of the primary survey conducted in the paper reveal that the individuals’ attitude to use discount coupons was skewed towards weekends and special occasions rather than on daily usage. It was also observed that the couponing sites have target audiences across geographies, ethnicities, gender and generations. Thus, the manufacturer of products and services are using the new success phenomenon of selling distress inventory to value conscious consumers. As the industry is in the stage of nascence, therefore, the players also need to map their own success stories rather than following a proven track.